TEACHER’S QUESTIONING STRATEGY IN ENGLISH CLASSROOM INTERACTION - Putri, Aryanti Anna; Erlita, Yeni (Universitas Negeri Medan, 2023)
This research aims to analyze Teacher’s Questioning Strategy and Student Response in English Classroom Interaction of Grade VIII at SMP Imelda Medan. The subject of this study were two teachers and two classes of Grade VIII at SMP Imelda Medan. This research used descriptive qualitative design as a research method. The data were collected by doing observation to the classroom, interview to the two English teachers, and record English teaching learning process. The study focused on analyzing the three research questions in this study, they are the teacher’s way in apply questioning strategies in English classroom interaction, teachers’ reason in the use of questioning strategies in English classroom interaction, and how the student’s response to teacher questions. Using Xuerong theory where questioning strategy is divided into 2, namely Question-Planning Strategy and QuestionControlling Strategy, findings of the observation, interview and video recording showed that the two English Teachers in SMP Imelda Medan mostly used Question-controlling Strategy. The researcher also analyzed student’s responses in two classes of grade VIII. Based on the observation in the classroom and video recording, most students were silent when teachers were asking them. Only some students were active in giving responses, those mostly used cognitive in answering the question from teachers. Based on the interview with the teachers, the both teachers have similar purposes, they want to know students understanding, involving in teaching learning process and make the learning atmosphere comfortable and interesting. In addition, teacher 1 is more dominant in giving questions to all students in the class while teacher 2 gives questions to students individually.